Early grade pupils’ development of Mathematics skills: Perceived challenges and culturally relevant strategies for parental involvement (Educational Dimension, 2024)
The current study investigated challenges facing parental involvement and culturally relevant strategies for improving parental involvement in the development of mathematics skills among grade two pupils. A phenomenological qualitative design was employed. A semi-structured interview was used to gather data from 12 early-grade teachers and ten heads of schools. Focused group discussion (FGD) was used to collect data from 63 parents. Thematic analysis procedures guided the data analysis procedure, which was aided by pivotal analysis. The study findings revealed that teachers focused on parents’ negative attitude towards the subject while parents reported lack of time and economic hardship as factors affecting their participation in engaging in children’s mathematics learning. However, all participants agreed that parents’ mathematics knowledge is a factor that affects their involvement. Regardless of the participants’ category, the provision of interactive mathematics homework and communication through parents’ meetings (group and individuals) were regarded as the best strategies for involving parents in learners’ development of mathematics skills. The study concludes that the parents agree with the critical role of their involvement despite the challenges facing parental involvement. Therefore, the study recommends that awareness programs and the use of interactive mathematics homework activities are critical to improved parental involvement in their children’s learning.
Keywords: parental involvement; mathematics; early grade learners